Testing a real-time intelligent evacuation guiding system for complex buildings. (December 2020) - Balboa, Adriana; González-Villa, Javier; Cuesta, Arturo; Abreu, Orlando; Alvear, Daniel
Highlights: We present an intelligent evacuation guiding system. Real-time intelligence and hard components are integrated. The system is tested in a building using participants. Evacuation improves significantly. Limitations are discussed for further research. Abstract: A recent challenge in life safety is to improve evacuee's performance using technology. Here we propose an intelligent evacuation guiding system for complex buildings. It uses information from fire protection systems, and calculates the optimal evacuation routes from real-time simulations to guide evacuees by dynamic signage through safest and fastest available paths. The proposed system was tested in a multi-enclosure building using participants. We found that 89% of participants followed the emergency exit signs. The reported results also indicate that the system may have a positive impact on evacuation time (reduced from 28.41% to 59.79% with the system). We also found that participants moved significantly faster when the system was in use. These findings support the hypothesis that, in practice, smart egress systems improve evacuation behaviour. Practical limitations of the tested system are discussed to define further research.